Search for long-lived heavy charged particles using a ring imaging Cherenkov technique at LHCb - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (The European physical journal. C, Particles and fields, 2015)
A search is performed for heavy long-lived charged particles using 3.0 $${\rm fb}^{-1}$$of proton-proton collisions collected at $$\sqrt{s}$$$$=
Gesehen am 21.07.2021
The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 664 weitere]